Analysis of the microbiota composition in the genital tract of infertile patients with chronic endometritis or endometrial polyps - Liang, Junhua; Li, Meng; Zhang, Lei; Yang, Yang; Jin, Xia; Zhang, Qiongqiong; Lv, Tao; Huang, Zhenyu; Liao, Qinping; Tong, Xiaowen (Frontiers in Cellular and Infection Microbiology, 2023)
Abstract Background: The current research shows that chronic endometritis and endometrial polyps have a higher incidence in infertility patients, and the occurrence of these two diseases is related to changes in the microbial flora of the reproductive tract. We aim to determine the composition and changing characteristics of the microbiota in the reproductive tract (especially the endometrium) of patients with chronic endometritis or endometrial polyps, in order to find the correlation between it and the occurrence of diseases. Methods: This study is a prospective observation study. Using 16S rRNA gene sequencing and pathological examination, we analyzed genital tract biopsy samples of 134 asymptomatic infertility patients receiving assisted reproductive therapy before embryo transfer. Results: Compared with the normal control group, the intrauterine microecology of patients with endometrial diseases such as chronic endometritis and endometrial polyps has changed. Lactobacillus, the dominant flora of female genital tract, showed a change in abundance in patients with endometrial diseases. Endometrial microbiota composed of Staphylococcus, Gardnerella, Atopobium, Streptococcus, Peptostreptococcus, Chlamydia, Fusobacterium, Acinetobacter, etc. are related to chronic endometritis and endometrial polyps. Conclusions: The results showed that, compared with the normal control group, the endometrial microbiota of infertility patients with chronic endometritis or endometrial polyps did have significant changes in the relative abundance distribution of species, suggesting that changes in local microecology may be an important factor in the occurrence of disease, or even adverse pregnancy outcomes. The further study of endometrial microecology may provide a new opportunity to further improve the diagnosis and treatment strategy of chronic endometritis.